1997
DOI: 10.1080/00288233.1997.9513270
|View full text |Cite
|
Sign up to set email alerts
|

Pasture management to minimise the detrimental effects of pre‐lamb shearing

Abstract: The purpose of this study was to examine whether the performance of pre-lamb shorn sheep is influenced by pasture allowance in the immediate post-shearing period and whether the relationship between performance and pasture allowance differs according to whether the ewes are shorn by standard comb or cover comb. The trial was replicated across two years to allow for climatic variations between years. Fifty-four ewes were used in each year in a 3 × 3 × 2 factorial design with three shearing treatments (standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Although smaller responses have been observed under pasture conditions in a temperate climate (i.e. Cloete et al, 1994), the majority of literature sources found no improvements in growth or weaning weight under pastoral conditions (Dabiri et al, 1994;1995;Cloete & Durand, 1996;Husain et al, 1997). From these references it appears as if growth responses in the progeny of ewes shorn prior to lambing are transient and unpredictable, although they may occasionally be present.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although smaller responses have been observed under pasture conditions in a temperate climate (i.e. Cloete et al, 1994), the majority of literature sources found no improvements in growth or weaning weight under pastoral conditions (Dabiri et al, 1994;1995;Cloete & Durand, 1996;Husain et al, 1997). From these references it appears as if growth responses in the progeny of ewes shorn prior to lambing are transient and unpredictable, although they may occasionally be present.…”
Section: Discussionmentioning
confidence: 98%
“…Results of studies conducted under free-ranging conditions in temperate areas are much less consistent. Birth weight responses are variable under these conditions (Dabiri et al, 1995;Husain et al, 1997). In a recent study, Kenyon et al (1999) not only found that responses in birth weight varied under outdoor conditions, but also that the realized response in groups shorn prior to lambing could be related to the mean birth weight of the control group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both factors are known to affect the ELR by increasing lamb mortality (Olaechea et al, 1981;Bellati and von Thu¨ngen, 1988;Coronato, 1999). Management practices, such as stocking rate, mating time, supplementary feeding and shearing time, are also known to affect ELR (Rattray and Jagusch, 1978;Husain et al, 1997;Golluscio et al, 1998b). There are also methodological constraints that could account for the unexplained residual.…”
Section: Article In Pressmentioning
confidence: 95%
“…The IRR is the discount rate at which the net present value is 0 (Gittinger 1982 (Table 1). Direct costs for the trials were based on the budgets submitted in the research proposals, the "Materials and Methods" sections of related publications Holmes et al 1992;Dabiri et al 1995aDabiri et al , 1995bBurnham et al 1996;Husain et al 1997), and personal communication with the authors of these papers. The labour contribution by postgraduate students was costed at technician rates to fully reflect the cost of the research.…”
Section: Model Developmentmentioning
confidence: 99%